Electron-related optical responses in triple δ-doped quantum wells. Issue 5 (4th March 2019) - Ungan, F.; Mora-Ramos, M. E.; Kasapoglu, E.; Sari, H.; Sökmen, I.
ABSTRACT: A detailed theoretical study on the electron-related optical responses in triple δ -doped GaAs quantum wells in the presence of non-resonant, monochromatic intense laser field is presented. For this purpose, we first obtained the bound subband energy levels and their corresponding envelope wave functions of the structure for different central doping concentrations within the effective-mass approximation. Then, we calculate the effect of the non-resonant intense laser field on the optical properties of this structure using the compact-density-matrix approach via the iterative method. We found that the optical absorption coefficients and refractive index changes in the triple δ -doped GaAs quantum well can be modulated by changing the central doping concentration and the intensity of the non-resonant, monochromatic laser field. In addition, it is shown that a sufficiently intense laser field suppresses the multiple quantum well configuration towards a single potential well one and the optical response becomes practically independent of the δ -doping concentration.